PERILAKU SINTAKSIS VERBA BAHASA INDONESIA: LINGKUP KLAUSA - Muhammad Darwis (Nady Al-Adab : Jurnal Bahasa Arab, 2008)
A verb is a word category wich us the most used in sentence arrangement. The word category has morphological, syntactic, and semantic behaviors. In this study the verb analysis is focused on syntactic behaviors point of vieuw. The data is taken from Indonesian ordinary register, used in daily activities either it isused in spoken and written language, or those are taken by the researcher’s intuition for the researcher is the native speaker of Indonesia. The result of the research shows that viewing from syntactic point of vieuw, Indonesian verbs are the entity that fill all syntactic function, i.e. subject (S), predicat (P), object (O), complement (C), and lokative (L).  And, Indonesian verb ha also function appositive and attributive function is known as serial verb or complex verb.